Efek Ekstrak Kulit Mangga Arumanis terhadap Penurunan Edema Kaki Mencit Putih Jantan yang Diinduksi Karagenin - Ongky Dyah Anggraini; Cicih Komariah; Aris Prasetyo (Pustaka Kesehatan, 2018)
Mango is a plant contains many active compounds with health benefits. Total phenolic content of mango peel is higher than mango flesh, with its major component are mangiferin and quercetin. Quercetin has anti-inflammatory effects through the inhibition of inflammatory mediators are serotonin, bradykinin, histamine and prostaglandin, possibly could reduce oedema as a sign of inflammation. This study used carrageenin to induce inflammation by making paw oedema in mice. The aim of this research was to know the effect of arumanis mango peel extract to reduce paw oedema in white male mice. The was quasi experimental study with 7 study groups. Spearman analyses showed a correlation with significance of (p= 0.003) that mean it has a significant correlation (p <0.01) at the 330th min. Spearman correlation coefficients was 0,632, indicated that the dose of extract and paw oedema have strong correlation. It can be concluded that mango peel extract has effect for reducing paw oedema in white male mice, with the smallest dose was 1,002mg / gBW. Keywords: mango, quercetin, paw oedema